2016
DOI: 10.3390/nu8120800
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic Effect of Opuntia ficus-indica var. saboten Is Due to Enhanced Peripheral Glucose Uptake through Activation of AMPK/p38 MAPK Pathway

Abstract: Opuntia ficus-indica var. saboten (OFS) has been used in traditional medicine for centuries to treat several illnesses, including diabetes. However, detailed mechanisms underlying hypoglycemic effects remain unclear. In this study, the mechanism underlying the hypoglycemic activity of OFS was evaluated using in vitro and in vivo systems. OFS treatment inhibited α-glucosidase activity and intestinal glucose absorption assessed by Na+-dependent glucose uptake using brush border membrane vesicles. AMP-activated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…The up-regulated expression of LOXs in GS is likely to provide sufficient nutrient preparation for pod development. Combined with the high expression of several energy- and substance-related transporter genes, which play critical roles in nutrient uptake and signal transduction (Leem et al, 2016 ), exogenous calcium probably promotes nutrient storage in the aerial gynophores, ascertaining the early development of pod.…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulated expression of LOXs in GS is likely to provide sufficient nutrient preparation for pod development. Combined with the high expression of several energy- and substance-related transporter genes, which play critical roles in nutrient uptake and signal transduction (Leem et al, 2016 ), exogenous calcium probably promotes nutrient storage in the aerial gynophores, ascertaining the early development of pod.…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharide ODP-Ia has been isolated from Opuntia dillenii Haw., and this was shown to have antihyperglycemic effects through the protection of the liver from peroxidation damage and through the maintenance of tissue function, thereby improving the sensitivity of target cells to insulin ( Zhao et al, 2011 ). Recent study conducted on murine model suggested that Opuntia ficus-indica treatment acts by inhibiting glucose absorption from the intestine and enhancing glucose uptake from insulin-sensitive muscle cells through the AMPK/p38 MAPK signaling pathway ( Leem et al, 2016 ). Findings of a recent study conducted on Mexican patients with type 2 diabetes suggest that O. ficus-indica (L.) Mill.…”
Section: Herbal Products and Secondary Metabolitesmentioning
confidence: 99%
“…5A, B). AMPK induces GLUT4 recruitment to the plasma membrane by activating its downstream effector, p38 MAPK, which is an insulin-independent mechanism for GLUT4 translocation (Leem et al, 2016). Increased free fatty acids in the blood are another element that induces insulin resistance in target cells.…”
Section: Wgd Reduces Lipid Accumulationmentioning
confidence: 99%
“…AMP-activated protein kinase (AMPK) is a major protein involved in regulation of energy homeostasis in cells (Hardie et al, 2012). Activation of AMPK not only recruits GLUT4 to the cell membrane through phosphorylation of p38 mitogen-activated protein kinase (MAPK) but also reduces synthesis of malonyl-CoA or a precursor of free fatty acids by inactivating acetyl-CoA carboxylase (ACC) (Day et al, 2017;Leem et al, 2016;Smith et al, 2016).…”
Section: Introductionmentioning
confidence: 99%